Immunohistochemical assessment of E-cadherin, β-catenin, CEACAM-1 and PTEN: tumor progression markers in melanoma Análise imuno-histoquímica dos marcadores de progressão tumoral, E-caderina, β-catenina, CEACAM-1 e PTEN em melanomas - Juliana Elizabeth Jung; Raul Anselmi Júnior; Lucas Gennaro; Fernanda El Ghoz Leme; Ana Paula Camargo Martins; Carlos G. Hirth; Luiz Fernando Bleggi Torres; Lúcia de Noronha (Sociedade Brasileira de Patologia Clínica, 2010)
INTRODUCTION AND OBJECTIVE: The aim of the present study is the immunohistochemical assessment of tumor progression markers (E-cadherin, β-catenin, CEACAM-1 and PTEN) in primary cutaneous melanomas and their correlation with prognostic factors. METHOD: Primary lesions in patients with cutaneous melanoma were recorded as to clinical data (age, gender, location and metastases) and anatomopathologic data (Breslow, Clark level, margins, histological type, mitosis, ulceration, regression, satellitosis and TIL type). It was made a comparison between immunohistochemical expression of the markers and prognostic and anatomopathologic factors. RESULTS: Breslow thickness was > 1 mm (thick) in 21 patients (48.83%) and < 1 mm (thin) in 22 (51.16%). There was a higher CEACAM-1 positive expression in thick melanomas than in thin ones (p = 0.002). There was a more frequent E-cadherin (p = 0.008), b-catenin (p = 0.001) and PTEN (p = 0.005) positive expression in thin melanomas than in thick ones. There was a more frequent CEACAM-1 positive expression in superficial (p = 0.003) and deep (p = 0.002) samples of thick melanomas than in thin ones. No statistically significant differences between clinical and histopathological data were found when comparing patients with (n = 6) and without metastasis (n = 15). DISCUSSION AND CONCLUSION: There was a higher positivity for E-cadherin, b-catenin and PTEN in thin melanomas, whereas there was a higher positivity for CEACAM-1 in thick melanomas. INTRODUÇÃO E OBJETIVO: O objetivo do presente estudo está na avaliação imuno-histoquímica de marcadores de progressão tumoral (E-caderina, β-catenina, CEACAM-1 e PTEN) em melanomas cutâneos primários e sua correlação com fatores prognósticos. MÉTODO: Lesões primárias de pacientes portadores de melanoma cutâneo foram tabuladas quanto a dados clínicos (idade, sexo, localização e metástases) e anatomopatológicos (Breslow, nível de Clark, margens, tipo histológico, mitoses, ulceração, regressão, satelitose e tipo de TIL). Foi realizada comparação da expressão imuno-histoquímica dos marcadores em estudo com fatores prognósticos clínicos e anatomopatológicos. RESULTADOS: Breslow foi > 1 mm (espesso) em 21 pacientes (48,83%) e ≤ 1 mm (fino) em 22 (51,16%). CEACAM-1 foi mais positivo em melanomas grossos que em finos (p = 0,002). E-caderina (p = 0,008), β-catenina (p = 0,001) e PTEN (p = 0,005) foram mais frequentemente positivos em melanomas finos que em grossos. CEACAM-1 foi mais frequentemente positivo nas porções superficiais (p = 0,003) e profundas (p = 0,002) dos melanomas grossos que nas dos finos. Não houve diferenças estatisticamente significativas entre dados clínicos e histopatológicos quando comparamos os pacientes com (n = 6) e sem (n = 15) metástases. DISCUSSÃO E CONCLUSÃO: Observou-se maior tendência de positividade para E-caderina, b-catenina e PTEN em melanomas finos. Por sua vez, CEACAM-1 demonstrou maior frequência de positividade nos melanomas grossos.